AR and YAP crosstalk: impacts on therapeutic strategies in prostate cancer - Zheng, Guansong; Yan, Zhaojie; Zou, Junrong; Zou, Xiaofeng; Chai, Keqiang; Zhang, Guoxi (Frontiers in Oncology, 2025)
Prostate cancer ranks as one of the most common types of cancer affecting men worldwide, and its progression is shaped by a diverse array of influencing factors. The AR signaling pathway plays a pivotal role in the pathogenesis of prostate cancer. While existing anti-androgen treatments show initial efficacy, they ultimately do not succeed in halting the advancement to CRPC. Recent studies have identified alterations in the Hippo-YAP signaling pathway within prostate cancer, highlighting intricate crosstalk with the AR signaling pathway. In this review, we examine the interactions and underlying mechanisms between AR and YAP, the key molecules in these two signaling pathways. AR regulates the stability and function of YAP by modulating its transcription, translation, and phosphorylation status, while YAP exerts both promotional and inhibitory regulatory effects on AR. Based on these findings, this paper investigates their significant roles in the onset, progression, and therapeutic resistance of prostate cancer, and discusses the clinical potential of YAP in prostate cancer treatment.